Nesting and exploitation of the Olive Ridley Sea Turtle at Escobilla Beach, Oaxaca, Mexico - Cervantes-Hernández, Pedro; Pérez-Vives, Eduardo; Gómez-Ponce, Mario Alejandro (Revista Ciencias Marinas y Costeras, 2017)
The exploitation of Lepidochelys olivacea along the Mexican Pacific has not been assessed since 1959. In addition, nesting season at Escobilla beach has only been partially documented. These two issues were analyzed with the methods recommended in the literature (mortality analysis and time series) using a database with total catch from January 1978 to May 1990. Net trends in the abundance of males and females descended over the study period, which led to the conclusion that the population was overexploited. Natural mortality rate was much lower compared to fishery mortality rate, the latter affecting both sexes with the same intensity. A complete nesting season spanned from August to January, with maximum abundance in November. As indicated in the literature, the nesting season of the Olive Ridley Sea Turtle in the Gulf of Tehuantepec (GT) coincided with the reproductive season of brow shrimp Farfantepenaeus californiensis (from July to February, with maximum spawning between October/November). In the GT shrimp fishing season is from September/October to March/April, completely overlapping the nesting season. Simultaneous fishing of the marine turtle (explained here) and shrimp caused overexploitation of L. olivacea. Shrimp fishery made L. olivacea a common species in the accompanying fauna. Consequently, turtle excluders were and continue to be used.